Fulminant case of neuromyelitis optica spectrum disorder initiated with area postrema symptoms. Issue 3 (9th March 2016) - Takahashi, Yoshiaki; Manabe, Yasuhiro; Nakano, Yumiko; Yunoki, Taijun; Kono, Syoichiro; Narai, Hisashi; Omori, Nobuhiko; Abe, Koji
Abstract: We report a 59‐year‐old man with intractable vomiting and hiccups, syndrome of inappropriate antidiuretic hormone secretion, quadriparesis, and encephalopathy of a short duration after the first episode as a result of neuromyelitis optica spectrum disorder. Magnetic resonance imaging showed high‐intensity areas in the hypothalamic, periventricular areas, and the presence of continuous lesions from the brainstem to the spinal cord. Intractable vomiting and hiccups should be considered as a hallmark of an exacerbation. Attentive consideration might be required, because the early initiation of treatment could prevent a subsequent neurological disorder.